2018
DOI: 10.1016/j.pepi.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

New numerical approaches for modeling thermochemical convection in a compositionally stratified fluid

Abstract: Seismic imaging of the mantle has revealed large and small scale heterogeneities in the lower mantle; specifically structures known as large low shear velocity provinces (LLSVP) below Africa and the South Pacific. Most interpretations propose that the heterogeneities are compositional in nature, differing in composition from the overlying mantle, an interpretation that would be consistent with chemical geodynamic models. The LLSVP's are thought to be very old, meaning they have persisted throughout much of Ear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…In other words, it is unstable [12] and perturbations due to different numerical methods can yield vastly differing results. In fact, in [58] we demonstrated that it suffices to change only the algorithm with which the composition variable C is advected in order to obtain clearly different results at the same output time. For example, see Figure 11 of [58] or compare Figures 5(c)-(d) of [59] to our results here or in [58] or to the results in [73].…”
Section: Mantle Convection Benchmark Problemsmentioning
confidence: 94%
See 2 more Smart Citations
“…In other words, it is unstable [12] and perturbations due to different numerical methods can yield vastly differing results. In fact, in [58] we demonstrated that it suffices to change only the algorithm with which the composition variable C is advected in order to obtain clearly different results at the same output time. For example, see Figure 11 of [58] or compare Figures 5(c)-(d) of [59] to our results here or in [58] or to the results in [73].…”
Section: Mantle Convection Benchmark Problemsmentioning
confidence: 94%
“…See [27] for a description of this algorithm in ASPECT and a comparison with the advection method with entropy viscosity described above. Also see [58] for a comparison of these two methods with the VOF method described here and a particle method for modeling the solution of the composition equation (22).…”
Section: Discretization Of the Composition Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…At this point need is to mention the two main classes of VOF methods: methods that try to reconstruct exactly the interface between fluids (e.g. Puckett et al 2018), which requires significant computational time, and methods that do not, such as in the present approaches with JADIM and OpenFOAM. With no interface reconstruction, the thickness of the interfacial region is defined by 0 < C i < 1, and typically occupies two to three grid cells.…”
Section: The Vof Methodsmentioning
confidence: 99%
“…This motivates the use of a volume-of-fluid (VOF) method, dedicated to the conservation of chemical interfaces. Recently, Puckett et al (2018) compared a VOF method (using interface reconstruction) against other standard methods in models of mantle convection. They qualitatively studied two-layer Rayleigh-Taylor and Rayleigh-Bénard systems in 2-D, and concluded that their VOF method may be the most appropriate method for modelling interfaces separating chemical compositions.…”
Section: Introductionmentioning
confidence: 99%